Increased single strand breaks in DNA of lymphocytes from diabetic subjects. - Lorenzi, M (1987)
Certain aspects of the chronic complications of diabetes suggest that, with time, the abnormal metabolic milieu leads to irreversible changes in some cell populations. Since we have previously observed that high glucose concentrations induce an increase in single strand breaks in the DNA of cultured human endothelial cells, we have investigated whether the same abnormality occurs in cells derived from the in vivo diabetic environment. Peripheral blood lymphocytes obtained from 21 type I diabetic patients and age- and sex-matched controls were tested for rate of unwinding in alkali (a measure of DNA single strand breaks). The patients were subdivided into two groups on the basis of glycohemoglobin values above or below 9%. The group with glycohemoglobin values of 12.9 +/- 2.4% (mean +/- SD), but not the group with glycohemoglobin values of 7.4 +/- 1.5%, showed accelerated unwinding of lymphocyte DNA when compared to controls (P less than 0.01). These studies suggest that poorly controlled diabetes may result in DNA lesions, whose impact on long-term complications deserves to be investigated.